Pengenalan dan Pemanfaatan Aplikasi Mendeley untuk Penulisan Karya Ilmiah Mahasiswa Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Kependidikan, Universitas Jambi - Nurfadilah, Nurfadilah; Gati Ningsih, Arum; Oktri Wini, Lusia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
The community service activity carried out is the introduction and training of Mendeley which is used in scientific papers. The goal is to introduce Mendeley so that students have knowledge and they able to utilize this application. The participants in this training were 33 students of the Indonesian Language and Literature Education study program, FKIP, Jambi University. The methods used are lecture, question and answer, and practice. Participants are guided to directly download, create a Mendeley account, and connect it MS Word. based on the posttest results, it is known that 97% of the 33 respondents can use Mendeley in writing scientific papers. The follow-up to this activity is to conduct similar training for new students of the Indonesian Language and Literature Education study program, FKIP, Jambi University every new academic year. This is done because writing scientific papers cannot be separated from the daily lives of students and lectures. Using Mendeley can make it easier for users to cite and compile bibliography which is very important in writing scientific papers.